Dukungan Lintas Sektor dalam Pencegahan Stunting melalui Posyandu di Kota Yogyakarta - Putri Kinayungan, Utami; Hasanbasri, Mubasysyir; Siwi Padmawati, Retna (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2024)
The prevalence of stunting has decreased, but is not yet in accordance with WHO standards. There has been a lot of research on the role of the community through community based services in efforts to improve nutritional status and most of them recommend cross-sectors. The aim of this research is to identify and analyze forms of cross-sector support in preventing stunting. This type of research is qualitative with a case study approach. Data collection was carried out by in-depth interviews with mothers of toddlers, health workers at community health centers, posyandu and PKK cadres, as well as sub-district officials using a purposive sampling method. Data analysis was carried out by open coding using the OpenCode 4.03 application. The research results show that cross-sector support in preventing stunting is realized in the form of: health workforce, service delivery and financing. Health workforce is realized in empowering cadres and TPK in providing education, assisting toddlers and making posyandu reports. Service delivery is realized in measuring body weight and height, carrying out validation, following up on cases of malnourished toddlers by conducting examinations at community health centers, providing medicine and multivitamins, as well as PMT for toddlers. Financing is realized by high levels of community self-reliance in providing financial support for posyandu activities, Health Operational Assistance (BOK) from the Central government for socialization and cadre training activities, sub-district APBD for stunting PMT, and the Health Service for cadre incentives.